The Improvement in Listening Skills of Children Aged 5-6 Years in Guidance for Kids Kindergarten Using the Ged Aplication - Yunita, Yunita; Puridawaty , Brigita (Kirana Publisher (KNPub), 2024)
The purpose of this study is to determine the improvement in listening skills of children aged 5-6 years in Kindergarten Guidance For Kids Using the GED Aplication. The research design used is quantitative research with a Pre-Experimental approach using the One Group Pretest-Posttest design. The sample for this study consists of 10 children from group B. The instrument used is an observation sheet. Data collection techniques in this study use observation and documentation techniques, while data analysis in this study uses SPSS 20. Based on the research results, it is shown that there is the improvement in listening skills of children aged 5-6 years in Kindergarten Guidance For Kids Using the GED Aplication. This can be seen after treating the children three times; they can listen attentively, interpret, and understand meaning. Furthermore, it is evident from the results of the Paired Sample Test statistical analysis with a sig value (2-tailed) of 0.002 < 0.05, which means that the null hypothesis (Ho) is rejected, and the alternative hypothesis (H1) is accepted. Therefore, it can be concluded that there is the improvement in listening skills of children aged 5-6 years in Kindergarten Guidance For Kids Using the GED Application.